A new novel nonsense mutation in AIPL1 in a LCA4 family. (4th July 2019) - Wan, Ling; Xiang, Li; Wang, Haixin; Shi, Yi; Jiang, Dan; Hao, Fang; Huang, Lulin
ABSTRACT: Purpose : To investigate the disease-causing gene in a Chinese family with Leber congenital amaurosis 4 (LCA4). Materials and methods : Four members of an LCA family underwent ophthalmological examination and systemic assessment. DNA samples were obtained from their peripheral blood. Whole exome sequencing (WES) was performed in the two patients. After data filtering, Sanger sequencing was performed to verify the mutation within this family. Results : The two patients were diagnosed as having LCA4 and with keratoconus (KCN). The older brother also has intellectual disability, epilepsy, Tourette syndrome and an abnormal gait, while the younger one has an abnormal bulge at the end of his sternum. A novel p.Gln81* mutation in the AIPL1 gene was determined as causing LCA4 in this family. Protein structure change prediction showed AIPL1 p.Gln81* mutation coded a very short AIPL1 peptide and could not form a normal structure as an normal AIPL1 protein. Conclusion : Although KCN has been associated with LCA4, this type of LCA is typically moderate in severity and variable between patients. The present cases also have some systemic abnormalities.